Building the Foundation of Acceptance Book by Book: Lesbian, Gay, Bisexual, and/or Transgender-Themed Books for Grades K–5 Multicultural Libraries. (1st October 2016) - Knoblauch, Dee
Abstract: This article is an analysis of picture books and chapter books involving lesbian, gay, bisexual, and/or transgender characters. Over 30 picture and chapter books were reviewed, each of which would be appropriate for use in elementary classrooms. For grades K–2, several picture books highlight different types of families, including families that have two moms or two dads. For grades 3–5, four chapter books that subtly and matter-of-factly include same-sex parents or lesbian, gay, bisexual and/or transgender characters are recommended. A discussion focuses on the significance of including lesbian, gay, bisexual, and/or transgender families and characters in the school-sanctioned curriculum beginning in the elementary grades. Families with same-sex parents is an increasing demographic in the United States; an inclusive curriculum would allow all children to see their families represented. For elementary students with "traditional" families, an inclusive curriculum extends their conceptions of family, ideally building the foundation for acceptance.